Correction to: Cryoablation in the liver: how accurately does the iceball predict the ablation zone? - Young, Shamar; Abramyan, Artyom; Goldberg, Dan; Hannallah, Jack; Schaub, David; Kalarn, Salil; Fitzgerald, Zachary; Woodhead, Gregory (Abdominal Radiology, 2025)
The article focuses on a correction made to a previously published piece in Abdominal Radiology, specifically addressing a spelling error in the name of a co-author. The name "Art Abamyan" has been corrected to "Artyom Abramyan." The correction ensures the accuracy of the authorship in the article. Additionally, the publisher, Springer Nature, emphasizes its neutrality regarding jurisdictional claims in published maps and institutional affiliations.